Taking It Personally : Racism in the Classroom from Kindergarten to College. - Berlack, Ann (Teaching/learning social justice., 2011)
When Sekani Moyenda, an African American elementary school teacher, accepted an invitation to speak at a graduate education class, neither the students nor Ann Berlak, their professor, could guess that her presentation would spark an outpouring of emotion and a reexamination of race from everyone involved. The "encounter"--As it was called -- was an expression of Moyenda's anger at the institutionalized racism of our educational system, a system whose foundations are reinforced and whose assumptions about race are reproduced in the graduate school classroom. Forcing everyone involve.